Effects of the Nozzle Configuration with and without an Internal Guide Vane on the Efficiency in Cross-Flow Small Hydro Turbines (2024)
ABSTRACT: In this work, an experimental analysis of the performance of a cross-flow turbine, commonly referred to as a Michell–Banki turbine (MBT), is carried out for small-scale hydropower production in rural areas located in developing countries to support their social and economic development activities. The study investigates how the efficiency of the MBT is influenced by the presence or absence of a nozzle, along with variations in the internal guide vane (GV) and its angle. The runner had 26 blades that were arranged symmetrically in the periphery between two circular plates. The designed MBT had the ability to generate a maximum of 100 W of power at a water flow rate and a head of 0.009 m3/s and 0.6311 m, respectively. The experimental tests were carried out using a hydraulic bench. The turbine efficiency without the inner GV was found to be higher than that of the turbine with the inner GV; i.e., it was found that the utilization of the GV did not enhance the efficiency of the MBT due to the occurrence of a choking effect. A maximum hydraulic efficiency of 85% was achieved in the turbine without an inner GV in comparison with the efficiency achieved (77%) with this device and an optimum opening angle of the GV of 24◦ (75% of opening). In this regard, the GV design should be carefully carried out to improve the MBT efficiency. Additionally, the effect of the GV shape on the MBT performance should be experimentally investigated to obtain a more general judgment regarding the role of this device.